Entrepreneurship Competence Level of Organic Farmers in Yogyakarta Province - Dian Galuh Pratita; Irham Irham; Jangkung Handoyo Mulyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2018)
Business on organic farming is now growing rapidly. Entrepreneurship competence has an important role in improving the organic business growth. Therefore, the objectives of this study are 1) to determine personal competence level such as self confidence, creative, risk taking, focus on problem solving, interpersonal ability, and readiness to learn, 2) to analyze technical competence level such as input creation skills, increasing production skills, and enhancing quality skills, and 3) to know the management competence levels namely general planning abilities, monitoring and evaluation, networking, customer management and marketing management. This study was conducted in Bantul, Sleman, and Kulon Progo Districts of Yogyakarta Province among organic rice, fruit, and vegetable farmers. A purposive technique was used to select 90 farmers. Normalized Rank Order method is applied to develop the scale, while Entrepreneurship Behavior Index (EBI) is used to assess the personal, technical, and management competence levels. The entrepreneurial dimension competence assumed different scale values from 5.72 to 1.00, with self confidence getting the highest scale. The result showed organic rice, fruit, and vegetable farmers have high in some of competence. Furthermore, it still need to be increased the management, personal, and technical competence among the organic farmers.